Có: \(\frac{a}{b}=\frac{b}{c}=\frac{c}{a}\)
Áp dụng tính chất của dãy tỉ số bằng nhau, ta có:
\(\frac{a}{b}=\frac{b}{c}=\frac{c}{a}=\frac{a+b+c}{b+c+a}=1\)
\(\Rightarrow b=a;c=b\)
\(\Rightarrow a=b=c\left(dpcm\right)\)
Thêm điều kiện : \(a+b+c\ne0\)
Áp dụng tính chất của dãy tỉ số bằng nhau, ta có :
\(\frac{a}{b}=\frac{b}{c}=\frac{c}{a}=\frac{a+b+c}{b+c+a}=1\)
\(\cdot\frac{a}{b}=1\Rightarrow a=b\)
\(\cdot\frac{b}{c}=1\Rightarrow b=c\)
\(\Rightarrow a=b=c\)
Vậy ...
\(\frac{a}{b}=\frac{b}{c}=\frac{c}{a}\)
=> ac = b2
ba = c2
bc = a2
=> b2 = c2 = a2
=> a = b = c
tíc mình nha!